Penerapan media video 世界 青年 说 [Shìjiè Qīngnián Shuō] pada matakuliah menyimak prodi pendidikan Bahasa Mandarin Universitas Negeri Malang - Sakti, Karina Fefi Laksana; Wulandari, Ike (2020)
In learning Mandarin, there are four skills: listening, speaking, reading, and writing. Listening is the first activity that must be mastered by learners. In pandemic conditions, it requires learning activities to be carried out online, thus educators are required to use more effective learning strategies such as learning media. This research is about the application of videos 世界 青年 说 [shìjiè qīngnián shuō] in Mandarin listening. This research is a type of qualitative descriptive research because this study aims to describe the application of video 世界 青年 说 [shìjiè qīngnián shuō] in the subject of Mandarin listening to the UM Mandarin Education Study Program. The application of video 世界 青年 说 [shìjiè qīngnián shuō] is carried out in three stages: first, primary, and final learning activities. Based on the results of the observations, it can be concluded that the teaching and learning activities of the listening subject by applying the video 世界 青年 说 [shìjiè qīngnián shuō] run smoothly in an orderly and conducive classroom situation. Based on the results of the interviews, students revealed that the video media 世界 青年 说 [shìjiè qīngnián shuō] was entertaining and not boring